Modern Methods of Surgical Treatment of Gastric Ulcer and Duodenal Ulcer (Texas Journal of Medical Science, 2022)
More than a century has passed since the production of the first perforating ulcer suturing operation in world practice. During this period, many researchers have put a lot of work into finding ways to reduce mortality and postoperative complications in perforated ulcers of the stomach and duodenum.